A Foresight Study of the Acceptance Level of Internet of Things (Iot) Among SMEs in Shah Alam, Selangor. - Nasaruddin, Safuan; Hashim, Fazian (Research in Management of Technology and Business, 2023)
The Internet of Things (IoT) is a global network of computer devices that connects the globe. It also has the potential to transform organizations by automating activities that range from inventory management to robotics and automation, therefore reducing costs and saving both time and money. Small and medium enterprises, as well as business industries in general, stand to profit from the expansion of IoT. However, many SMEs struggle to adapt the digital world. Hence, this study was aimed at identifying the factors and the level of acceptance of Internet of Things (IoT) among SMEs in Shah Alam, Selangor. STEEPV analysis will be used in the first phase to identify the factors and the level of acceptance on IoT among SMEs in Shah Alam, Selangor. In the second phase questionnaires and Statistical Package for Social Science (SPSS) statistical analysis were used to study the relationships between the factor and level of acceptance on IoT among SMEs. It is anticipated that the findings of this study would give important and insightful information to many businesses in relation to knowledge upon achieving competitive advantage during the emerging digital era. The result of the survey concluded that key driver “Effectiveness of Technology”, and secondly the key driver “Environment Sustainability”, these results were discovered from scenario building. The findings of this study will help small and medium-sized enterprises (SMEs) and other types of businesses that have the potential to adopt technology and enhance their financial performance, employee productivity, and customer relationships.